Implementation of an evidence based guideline reduces blood tests and length of stay for the limping child in a paediatric emergency department. Issue 1 (2nd March 2012) - McCanny, Peter J; McCoy, Siobhan; Grant, Tim; Walsh, Sean; O'Sullivan, Ronan
Abstract : Introduction: Acute non-traumatic limp is a common reason for children to present to the emergency department (ED). There is a wide differential diagnosis for these patients, and there are certain serious conditions which cannot be missed. An evidence based guideline for the 'limping child' was designed and the impact of guideline implementation on a number of specific, predefined quantitative outcomes was assessed. Methods: An initial retrospective chart review over 3 months was carried out for all patients presenting with acute non-traumatic limp. Following guideline introduction and implementation, information was gathered prospectively for a further 3 month period. Data outcomes between the two patient groups were then compared. Results: 110 patients met the criteria for inclusion: 56 pre-guideline and 54 post-guideline implementation. Baseline characteristics and diagnosis breakdown were similar in both groups. The rate of laboratory investigations was significantly reduced following guideline implementation (68% of patients pre-guideline, vs 48% post-guideline; (χ 2 ), p=0.03). The number of x-rays carried out was similar in each group (74 pre- vs 67 post-guideline, mean 1.32 vs 1.28; (χ 2 ), p=0.53). Length of time spent in the ED was significantly reduced following guideline implementation (median time 150 min pre- vs 82.5 min post-guideline; (χ 2 ), p=0.04). No cases of serious pathology were missed using the guideline. Conclusion: Implementation of an evidence based clinical practice guideline for the limping child in a paediatric ED reduced the overall time patients spent in the ED, reduced the need for unnecessary laboratory investigations and ensured that appropriate investigations were carried out on an individual patient basis.